Methods in empirical prosody research - Sudhoff, Stefan; Pappert, Sandra (Language, Context and Cognition, 2012)
Biographical note: Stefan Sudhoff, University of Leipzig, Germany; Denisa Lenertová, University of Leipzig, Germany; Roland Meyer, University of Regensburg, Germany; Sandra Pappert, University of Leipzig, Germany; Petra Augurzky, Philipps-Universität Marburg, Germany; Ina Mleinek, University of Leipzig, Germany; Nicole Richter, Friedrich-Schiller-Universität Jena, Germany; Johannes Schließer, University of Leipzig, Germany.